The Influence of Eastern and Western Values on The Thinking of Modern Youth - Umarov Khumoyunmirzo Zakhriddinbobur ogli (Frontline Social Sciences and History Journal, 2025)
This article explores the dynamic interplay between Eastern and Western cultural values and their influence on the cognitive and ideological development of modern youth. In an era defined by globalization, technological advancement, and cultural hybridization, the youth increasingly find themselves navigating a complex matrix of traditional and modern values.